NATURAL FOCAL DISEASES IN RUSSIA: MONITORING AND MAPPING - Svetlana Malkhazova; Dmitry Orlov; Varvara Mironova; Tatyana Kotova; Natalya Shartova (Geography, Environment, Sustainability)
The paper discusses a mapping method for compilation of maps for a medical-geographical Atlas of Russia “Natural Focal Diseases” and potential that this Atlas presents for assessment and monitoring of the epidemiological situation in a number of diseases. A series of analytical, integrated, and synthetic maps shows disease incidence in the population at both the national and regional levels for the last 15 years. The Atlas contains maps of the mean annual incidence of certain infections and maps of incidence dynamics and nosological profiles that allow detailed analysis of the situation for each of 83 subjects of the Russian Federation. The degree of epidemic hazard in Russia by naturally occurring is reflected in a synthetic medical-geographical map that allows one to estimate the risk of a disease manifestation in a given region.